Inhibition of Prothrombin, Thrombin and Autoprothrombin C with Enzyme Inhibitors - June Caldwell, M; Seegers, Walter H. (Thrombosis and Haemostasis, 1965)
Numerous chemical enzyme inhibitors were employed to determine the active polar groups in the prothrombin, thrombin and autoprothrombin C molecules. Prothrombin and autoprothrombin C activities were decreased by the reduction of disulfide bonds, but thrombin activity was affected only at higher concentrations of reducing agent. Amino groups were not essential for the activity of autoprothrombin C; however, the blocking of such groups decreased the activities of prothrombin and thrombin. The blocking of carbonyl groups decreased the activity of both prothrombin and autoprothrombin C, but thrombin was not inactivated by hydroxylamine. The activities of none of the three were decreased by sulfhydry] blocking agents. Nonspecific oxidizing agents reduced the activities of all three molecules ; however, oxidizing agents which specifically oxidize sulfhydryl groups, were incapable of decreasing the activities of prothrombin, thrombin or autoprothrombin C. The sulfhydryl groups are not essential for the activities of prothrombin, thrombin or autoprothrombin C.